Efektivitas fungsi pedestrian berdasarkan tingkat pelayanan trotoar pada ruas Jalan A.P. Pettarani Kota Makassar - Amir, Ummi Kartini; Massara, Asma; Syarkawi, Mukhtar Thahir (LPPM Universitas Pahlawan Tuanku Tambusai, 2025)
This research focuses on the effectiveness of pedestrian functions based on the level of sidewalk service on Jalan A.P. Pettarani, Makassar City. With rapid population growth and increasing vehicle volumes, the condition of pedestrian infrastructure is often neglected, resulting in serious problems in community mobility. This research aims to analyze the relationship between the level of sidewalk service and the effectiveness of pedestrian function using a quantitative research approach method with a sample size of 100 respondents. The research results show that the pedestrian flow variable (X3) does not have a significant effect on the effectiveness of pedestrian function, due to the dominance of motorized vehicles and poor sidewalk conditions. And the variables Pedestrian Density Walking speed (X1), Pedestrian density (X2) and Pedestrian space (X4) greatly influence the effectiveness of pedestrian function along the sidewalk on that road section. This research recommends improving infrastructure and enforcing regulations on sidewalk use to create a more pedestrian-friendly environment. It is hoped that these findings can become the basis for planning better transportation policies in Makassar City, as well as increasing awareness of the importance of pedestrian facilities in supporting community mobility